Saudi Arabia and Sri Lankas Expanding Economic Ties (Global Journal of Human-Social Science, 2023)
In January 22 2023 Sri Lanka s Minister of Foreign Affairs Ali Sabry visited Saudi Arabia and met the Kingdom s Minister of Foreign Affairs His Highness Prince Faisal bin Farhan Al Saud The two leaders discussed prospective ventures between Saudi Arabia and Sri Lanka which would have an impact on their bilateral ties with respect to economic engagement in a changing world order The visit is significant because it included discussions on areas including growing trade raising investment and promoting tourism On January 27 2023 the Agreement on Avoiding Double Taxation was signed between the two countries 1 Additionally Saudi Arabia proposed hiring up to 200 000 Sri Lankans in 2023 2 This paper analyses the current Saudi Arabia - Sri Lanka relations and looks at several potential areas of collaboration Moreover it discusses the shared interest of both countries in advancing their economic ties and highlights the challenges in this regard